1999
DOI: 10.1097/00007890-199901270-00005
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Swine Major Histocompatibility Complex Class I Molecules on Porcine Endothelium by Tumor Necrosis Factor-?? Reduces Lysis by Human Natural Killer Cells1

Abstract: These results imply that SLA class I molecules can bind to inhibitory receptors on human NK cells, and that these interactions can be augmented by increasing the level of SLA class I molecule expression on porcine endothelium. Strategies that can increase porcine endothelial cell expression of either swine or human major histocompatibility complex class I molecules may reduce human NK activity against porcine xenografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Other studies showed the involvement of the adhesion molecules CD2 and CD49d in NK cell triggering by porcine cells (17), but these may be secondary events to triggering mediated by Gal␣1,3-Gal and CD86. This protective effect would also be in accordance with observations from Kwiatkowski et al (29) that SLA I can play an inhibitory role through some killer Ig-related receptor. It would be interesting to assess these pathways within our system in a future study.…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…Other studies showed the involvement of the adhesion molecules CD2 and CD49d in NK cell triggering by porcine cells (17), but these may be secondary events to triggering mediated by Gal␣1,3-Gal and CD86. This protective effect would also be in accordance with observations from Kwiatkowski et al (29) that SLA I can play an inhibitory role through some killer Ig-related receptor. It would be interesting to assess these pathways within our system in a future study.…”
Section: Figuresupporting
confidence: 92%
“…IL-2-mediated activation of NK cells increases their cytotoxicity toward porcine cells (27,28). Even if swine leukocyte Ag (SLA) class I may have a protective role through recognition of inhibitory receptors on human NK cells (29), its effect is clearly overridden by activating signals. In the absence of human serum, human NK cells lyse xenogeneic porcine aortic endothelial cells (PAEC) Ͼ2-fold more than allogeneic HUVEC (30,31).…”
mentioning
confidence: 99%
“…Regarding the subsequent firm adhesion, b 2 -integrins such as CD11a/CD18 and CD11b/CD18 as well as interactions between CD49d and CD106 seem to be involved. Here, a role for CD2 expressed on human NK cells was also demonstrated by Kwiatkowski et al [43], while CD62L interactions appear to be less important than under flow conditions. Finally, the data also indicate that CD162 on human NK cells, CD62E on porcine EC, and CD31 on either cell type have no or only minor influence on the adhesion of human NK cells to porcine EC.…”
Section: Studies On Adhesive Interactions Between Human Nk Cells and supporting
confidence: 77%
“…Our results demonstrate that the expression of HLA-G in either microvascular (2A2) or aortic (PED) pEC provides only partial protection against NK cytotoxicity mediated by polyclonal NK lines, the NK92 cell line, and a panel of NK clones. Since it has been shown that human NK cells may be inhibited, although weakly, by SLA class I molecules (45), differences between HLA-G-transfected pEC and control pEC in the expression of SLA class I may theoretically also explain our results. However, comparable amounts of SLA class I molecules were found on the HLA-G-transfected pEC, and the reversion of the HLA-G-mediated protection observed in blocking experiments using an anti-HLA-class I Ab (data not shown) confirms the ability of HLA-G to inhibit NK cytotoxicity against pEC (25).…”
Section: Discussionmentioning
confidence: 58%